ASUPAN GIZI DENGAN PENGENDALIAN DIABETES PADA DIABETISI TIPE II RAWAT JALAN DI BLU PROF.DR.R.D.KANDOU MANADO - Olga Lieke Paruntu (Jurnal GIZIDO, 2012)
Diabetes is non communicable diseases that will increase in number and becomes thecause of a number of pain and death. Diabetes is becoming a fairly serious illness and getsattention because diabetes can cause complications that invade the entire body. Anincreasing number of diabetics is largely influenced by the lifestyle of the community.Diabetes also provide big economic burden influence for her treatment. The purpose of theshort term management of DM is the loss of a variety of complaints/symptoms of diabetesso that sufferers can enjoy a healthy and comfortable life. These goals can be achieved withgood metabolic control remains as reflected by its normal levels of glucose and lipid profile.The purpose of this research is to know the nutritional intake of the relationship with thecontrolling type II diabetes in outpatient diabetisi at BLU hospital Prof. Dr. r. d. KandouManado. The method used in this research include observational analytic with crosssectional design, implemented in July 2012. Samples are obtained in accidental sampling of31 people. Data analysis using SPSS 10.0 with Correlation test. Menukjukkanu uptake ofresearch results of energy, fat and carbs associated with control of blood glucose levels, butthe intake of protein is not related to the control of blood glucose levels. There is arelationship between intake of protein, carbohydrates and total cholesterol levels of control.There is no relationship between the intake of nutrients with the levels of LDL, HDL, andtriglyceride levels.